The impact of conditional cash transfer programs on indigenous households in Latin America: Evidence from PROGRESA in Mexico - Quiñones, Esteban J.; Roy, Shalini (International Food Policy Research Institute, 2016)
Conditional cash transfers(CCTs) are widely used antipoverty measuresin Latin America, and manysuch programs include indigenous beneficiaries.However, concerns have been raised that the indigenous poor,who have historically been marginalized,may not benefit from CCTsas much as the nonindigenouspopulation, owing to cultural as well as geographic factors. Even so, rigorous evidenceshowing this effect is limited. We assessedthis issue in the context of PROGRESA (Programa de Educación, Salud, y Alimenación), an integrated approach to poverty alleviation in Mexico, in which over one-thirdofbeneficiaries were indigenous at the program’s inceptionin 1998. A feature of the program’s initial targetingwasthat indigenous and nonindigenous beneficiaries were drawn from geographically similar areas, minimizing the potential for geographic factors to lead to differential impacts.Despite an extensive literatureshowing positive average impacts of PROGRESAon health and education outcomes, few studieshave disaggregatedthese effects by indigenous status. Using the randomized assignment of initial programrollout, we estimatedPROGRESA’simpactson a range of health and education indicators, distinctly for indigenous and nonindigenousbeneficiaries.We foundthat, as of November 2000, PROGRESA had significant impacts on many health and education indicators among both indigenous and nonindigenous households in our sample; in addition, in aggregateacross most indicators, these impacts werevery similar. Our results indicate thatif geographic disadvantage for indigenous households can be minimized(a nontrivial endeavor),cultural factors may not pose an intrinsic barrier to indigenous householdsbenefiting from CCTprograms, and as such, CCTs canpromote humancapital accumulation amongboth indigenous and nonindigenous households